Identifying Implementation Strategies for Integrating Drones into STEM and Career Technology Education CTE Programs - Timothy F. Slater (MDPI AG, 2024)
As drone technology is rapidly becoming accessible to school children in terms of both low cost and ease-of-use, primary and secondary school teachers are beginning to consider where modern drones can play an important role in schooling. To date, there is little empirical education research printed in the education research literature guiding innovative curriculum developers in the incipient domain of drone education. As a result, teachers interested in including emerging technologies in their classrooms are often at a loss of where to begin. Through clinical interviews with schoolteachers in the United States, our study identified five readily accessible "departure points" to include drones in contemporary STEM and vocational technology (CTE) school classrooms that help teachers address common curricular goals. Taken together, these interviews reveal that teachers using drones follow one of several distinct pathways as a first step toward achieving a widespread goal of teaching students to use modern technologies to construct, pursue, and communicate findings of fruitful research inquiries-the prevalence of which is not reflected in a comprehensive review of the literature. The five dominant pathways for starting a successful drone education emerging from the interview data were as follows: timed racing trials; precision flight obstacle courses; computer coding; videography; and domain-specific knowledge of drone operation laws and ethics.